2006
DOI: 10.1530/rep.1.01151
|View full text |Cite
|
Sign up to set email alerts
|

Role of Src homology 2 domain-mediated PTK signaling in mouse zygotic development

Abstract: Fyn and other Src-family kinases play an essential role at several steps during egg activation following fertilization of externally fertilizing species, such as marine invertebrates, fish, and frogs. Recent studies demonstrate that the requirement for Src-family kinases in activation of the mammalian egg is different from lower species, and the objective of this study was to test the role of the Fyn kinase in the mouse egg activated by intracytoplasmic sperm injection (ICSI). An Src homology 2 (SH2) domain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 47 publications
5
39
1
Order By: Relevance
“…Our recent studies have focused on the role of SFKs during oocyte maturation and fertilization [10,11,14]. The present data reinforce a role for Fyn kinase in what we suggest is an example of cortical maturation.…”
Section: Intracellular Localization and Dynamics Of Protein Phosphorysupporting
confidence: 87%
See 2 more Smart Citations
“…Our recent studies have focused on the role of SFKs during oocyte maturation and fertilization [10,11,14]. The present data reinforce a role for Fyn kinase in what we suggest is an example of cortical maturation.…”
Section: Intracellular Localization and Dynamics Of Protein Phosphorysupporting
confidence: 87%
“…Fyn knock-out oocytes fail to increase cortical phosphorylation of pTyr proteins Our studies of SFKs during meiotic maturation and fertilization have demonstrated an essential function for SFKs for proper organization of chromosomes and spindles [10,11,14]. Of the nine SFKs produced in mammalian cells, FYN kinase is expressed at very high levels in oocytes.…”
Section: Patterns Of Mpm2mentioning
confidence: 99%
See 1 more Smart Citation
“…Src, Yes, and Fyn are found in a broad range of mammalian cells, including oocytes (Sato et al 1996, Talmor-Cohen et al 2004, Mehlmann & Jaffe 2005, Meng et al 2006, McGinnis et al 2007, Zheng et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, SFKs mediate the fertilization-induced Ca 2+ response of the frog Xenopus (Sato et al 2000(Sato et al , 2006, albeit by different mechanisms than in other deuterostomes (Runft et al 2002). Conversely, although mammalian eggs express SFKs, such kinases are apparently not necessary for initiating Ca 2+ oscillations (Kurokawa et al 2004;Mehlmann and Jaffe 2005;Meng et al 2006;Tomashov-Matar et al 2007).…”
Section: Introductionmentioning
confidence: 99%